Mannitol challenge testing for asthma in a community cohort of young adults. Issue 4 (5th December 2016) - White, Elisha C.; de Klerk, Nicholas; Hantos, Zoltan; Priston, Monique; Hollams, Elysia M.; James, Alan; Sly, Peter D.; Holt, Patrick G.; Hall, Graham L.
ABSTRACT: Background and objective: Mannitol challenge testing is an established tool for clinical asthma diagnosis, and can be performed outside of specialized respiratory laboratories. Despite applicability in both clinical and non‐clinical populations, with different pre‐test asthma probabilities, differences in diagnostic properties have not been well explored. This study aimed to quantify the diagnostic utility of mannitol challenge testing for asthma in a community cohort and a symptomatic wheezing subset of this cohort. Methods: During the 22‐year follow‐up of the Western Australian Pregnancy (Raine) Cohort, 772 participants (384 males) completed mannitol challenge and skin prick testing and respiratory health questionnaires, of whom 148 reporting wheeze in the past 12 months were included in a wheezing subset. Results: Responsiveness to mannitol had low sensitivity (19%) and high specificity (97%) to identify current asthma in the complete cohort, with positive and negative predictive values (PPV and NPV) of 45% and 92%, respectively. Within the wheezing subset, sensitivity (19%) and specificity (94%) remained similar, but PPV increased to 79%, and NPV decreased to 52%. Conclusion: Our findings support previously reported high specificity and good PPV for mannitol challenge testing in symptomatic wheezing populations, and highlight the need for caution when interpreting mannitol test results in non‐clinical populations. Abstract : Mannitol challenge testing for asthma is increasingly used in non‐clinical populations outside specialized respiratory laboratories. This study found high specificity (94%) and good positive predictive value (PPV, 79%) in a wheezing population, but low PPV (45%) in a non‐clinical population. Caution is required when interpreting testing in non‐clinical populations. Watch the video abstract